Morphological transformation of Helicobacter pylori during prolonged incubation: association with decreased acid resistance. Issue 2 (February 1994) - Moshkowitz, M; Gorea, A; Arber, N; Konikoff, F; Berger, S; Gilat, T
Abstract : The survival of clinical isolates of H pylori at two cultural ages (two and four days) at pH 2, in the presence of different buffers, with and without urea, was investigated. It was found that the morphological changes which occur with longer incubation of H pylori have an inverse correlation with its resistance to an acidic environment. The finding that the addition of urea almost reversed this phenomenon and prolonged survival of the cultures emphasises the role of urea in the survival of H pylori in acidic environments.